Chromosome-Level Genome Assembly and Circadian Gene Repertoire of the Patagonia Blennie Eleginops maclovinus—The Closest Ancestral Proxy of Antarctic Cryonotothenioids - Chi-Hing Christina Cheng; Angel G. Rivera-Colón; Bushra Fazal Minhas; Loralee Wilson; Niraj Rayamajhi; Luis Vargas-Chacoff; Julian M. Catchen (Genes, 2023)
The basal South American notothenioid Eleginops maclovinus (Patagonia blennie or róbalo) occupies a uniquely important phylogenetic position in Notothenioidei as the singular closest sister species to the Antarctic cryonotothenioid fishes. Its genome and the traits encoded therein would be the nearest representatives of the temperate ancestor from which the Antarctic clade arose, providing an ancestral reference for deducing polar derived changes. In this study, we generated a gene- and chromosome-complete assembly of the E. maclovinus genome using long read sequencing and HiC scaffolding. We compared its genome architecture with the more basally divergent Cottoperca gobio and the derived genomes of nine cryonotothenioids representing all five Antarctic families. We also reconstructed a notothenioid phylogeny using 2918 proteins of single-copy orthologous genes from these genomes that reaffirmed E. maclovinus’ phylogenetic position. We additionally curated E. maclovinus’ repertoire of circadian rhythm genes, ascertained their functionality by transcriptome sequencing, and compared its pattern of gene retention with C. gobio and the derived cryonotothenioids. Through reconstructing circadian gene trees, we also assessed the potential role of the retained genes in cryonotothenioids by referencing to the functions of the human orthologs. Our results found E. maclovinus to share greater conservation with the Antarctic clade, solidifying its evolutionary status as the direct sister and best suited ancestral proxy of cryonotothenioids. The high-quality genome of E. maclovinus will facilitate inquiries into cold derived traits in temperate to polar evolution, and conversely on the paths of readaptation to non-freezing habitats in various secondarily temperate cryonotothenioids through comparative genomic analyses.